The Effects of Corrosive Chemicals on Corrosion Rate of Steel Reinforcement Bars: I. Swamp Water - Widanarko, Sulistyoweni; Ashadi, Henki W.; Wicaksono, Andri Krisnadi (UI Scholars Hub, 2002)
Most of infrastructures using steel concrete to reinforce the strength of concrete. Steel concrete is so vulnerable to chemical compounds that can cause corrosion. It can happen due to the presence of chemical compounds in acid environment in low pH level. These chemical compounds are SO4 2-, Cl-, NO3 -. There are many swamp area in Indonesia. The acid contents and the concentration of ion sulphate, chlorides, and nitrate are higher in the swamp water than in the ground water .The objective of this research was to find out the influence of corrosive chemicals in the swamp water to the steel concrete corrosion rate. There were two treatment used: (1) emerging ST 37 and ST 60 within 60 days in the ‘polluted’ swamp water, (2) moving the ST 37 up and down periodically in the ‘ polluted’ swamp water. Three variation of ’polluted’ swamp water were made by increasing the concentration of corrosive chemical up to 1X, 5X and 10X respectively. The corrosion rate was measured by using an Immersion Method. The result of Immersion test showed that chloride had the greatest influence to corrosion rate of ST 37 and ST 60 and followed by sulphate and Nitrate. Corrosion rate value for ST 37 is 24.29 mpy and for ST 60 is 22.76 mpy. By moving the sample up and down, the corrosion rate of ST 37 increase up to 37.59 mpy, and chloride still having the greatest influence, followed by sulphate and nitrate.